(untitled) (ARQUISUR Revista, 2011)
It is shown here the evaluation of the energy requests for the electromechanical interior conditioning of houses of social interest, considering the thermal behavior of ten types of houses of state and private developments, modelling and simulated by means of specific software. The target was to evaluate the thermal and energetic behavior, the degree of well-being of the users and the saving of energy produced on having materialized the walls that conforming the envelope of the houses with timber sandwich panels of forests cultivated with sustainable management in the Argentine northeast, in comparison with houses of conventional design and technology of bricks, in the cities of Corrientes and Resistencia, and also the incidence of such variables as the orientation, the form and the emplacement in the energy efficiency, and in the environmental efficiency of the construction. There tried to be analyzed the way in which the changes in the design of the houses’envelope, generate important differences in the final energy consumption of the houses, and to determine what are the strategies of improvement of the variables considered in the design of houses located in a warm - humid zone. Lower consumptions of electricity registered when the houses of traditional walls of bricks were replacing these walls by timber sandwich panels proposed.